Orange Juice Consumption Is Not Associated with Excess Weight Gain in a Large Prospective Cohort of US Children and Adolescents. (29th May 2020) - Sakaki, Junichi; Li, Jing; Melough, Melissa; Tamimi, Rulla; Chavarro, Jorge E; Chen, Ming-Hui; Chun, Ock
Abstract: Objectives: Given the conflicting evidence regarding fruit juice consumption and childhood obesity, we sought to evaluate associations between 100% orange juice (OJ) consumption and changes in anthropometric parameters in a large prospective cohort of US children and adolescents. Methods: Participants from the Growing Up Today Study II ( n = 7301) completed a baseline questionnaire in 2004 and follow-up questionnaires in 2006 and 2008. Data from these questionnaires were then used to assess mean 2-year changes in anthropometric characteristics in relation to OJ consumption. Changes in body mass index (BMI) percentile and height-for-age z-score (HAZ) were computed across OJ consumption categories using mixed linear regression modeling. Results: Girls' 2-year mean (SD) change in BMI percentile was not associated with OJ consumption after full adjustment: −0.44 (0.36) for OJ non-consumers, 0.20 (0.41) for 1–3 glasses/month, −0.04 (0.34) for 1–6 glasses/week, and −0.77 (0.62) for ≥1 glass/day ( P- trend = 0.49). Meanwhile, girls' 2-year mean (SD) change in HAZ was positively associated with OJ consumption: 0.03 (0.01) for non-consumers, 0.03 (0.02) for 1–3 glasses/month, 0.06 (0.01) for 1–6 glasses/week, and 0.09 (0.02) for ≥1 glass/day after full adjustment ( P -trend = 0.02). There were no significant associations in boys. Conclusions: These results indicate that OJ consumption was not associated with BMI percentile but was positively associated with HAZ change in girls, suggesting that OJ consumption is unlikely to contribute towards obesity. Funding Sources: This study was supported by the Florida Department of Citrus, an executive agency of the state of Florida.